12 STEPS AND ABSTINENCE: HOW DO I STAY SOBER? - HETENYI, Tamas; KOTTA, Ibolya (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2022)
The present study was conducted among 12-steps communities of recovery (Alcoholics Anonymous, Narcotics Anonymous) in Hungary. As these communities become more and more frequented, it is of interest to explore how recovering addicts implement their specific program of recovery and what psychological characteristics are affected by this process. The study presumed that longer time in abstinence predicted lower levels of chronic stress and higher levels of subjective well-being, given that participants were working actively on their sobriety/recovery. Thus, it was assumed that more intense work on sobriety would lead to lower levels of stress and higher levels of well-being. After filtration, N = 148 recovering addicts were included in the study. The participants completed a test-battery including queries on sobriety efforts (SEQ); Perceived Stress Survey (PSS-13) and the shortened version of WHO’s well-being questionnaire (WB15). The results show that abstinence doesn’t influence levels of stress neither in itself nor through active work on recovery. Nevertheless, a more intense work on sobriety (adhering to the 5 suggestions of 12 step program) predicted higher levels of subjective well-being. Recovering addicts commit themselves most actively to the recommendations of the 12-step communities during their first to five years of their abstinence. Our study makes a stand for anonymous recovery programs and argues that active efforts of maintaining sobriety are essential for sustainable recovery and long-term sobriety, and adherence to the five recommendations of these 12-step communities predict subjective well-being. Received: 2022 March 05; Revised: 2022 March 25; Accepted: 2022 March 28; Available online: 2022 May 5; Available print: 2022 May 30